"Avaliação hemodinâmica da artéria testicular de garanhões normais e com torção do cordão espermático" - Deborah Freitas Silva (2021)
Doppler ultrasonography is commonly used in andrological evaluation of humans and is a relevant method for monitoring testicular hemodynamics. However, in horse andrology it is scarcely used. Therefore, the aim of this study was to evaluate the blood flow pattern in testicular artery of normal stallions of different age groups and stallion’s whit 180° torsion of spermatic cord. Both testicles from 52 stallions (Mangalarga Marchador) were evaluate using spectral Doppler. Animals with normal testicles were divided in three age groups: normal young (NY=10), normal adult (NA=10), normal old (NO=10) and animals with torsion of spermatic cord in two age groups: torsion young (TY=10) and torsion adult (TA=8). Four stallions with hydrocele were evaluated separately. The values of resistive index (RI), pulsatility index (PI), peak systolic velocity (PSV), end diastolic velocity (EDV) and time average maximum velocity (TAMV) were measured in the supratesticular artery (Supra) and in capsular artery (Cap). The effect of the predictor variables presence of torsion, age group and side were assessed using mixed models, Pearson correlations were also applied to assess the association between pairs of variables. The results showed higher PSV Supra in NO compared to NY (P <0.041) and higher PI Supra in the left testicles of NO compared to the right testicles of NY and NA (P <0.001). Reduced RI Supra was observed in twisted testicles compared with normal testicles of young animals (P<0,001) and lower EDV Supra in contralateral testicles compared with normal testicles of adults animals (P<0,001). Reduction in the values of RI, PI and PSV and an increase in EDV were detected in the path of the testicular artery from Supra to Cap in all groups (normal, twisted and contralateral tescticles) of young and adult stallions. Hydrocele cases highlighted superior measurements of RI Supra in relation to stallions with bilateral spermatic cord torsion (P <0.033). In conclusion, lower testicular blood perfusion is observed in aged stallions. Moreover, testicles with hydrocele presents changes in blood flow, as well as, twisted testicles and contralateral testicles.